The Washington manual internship survival guide for PDA - Lin, Tammy L.; Mohart, John M.; Sakurai, Kaori A. (Philadelphia : Lippincott Williams & Wilkins, 2003)
The Washington manual internship survival guide is a small handbook written by the Washington University chief residents, residents and interns. This PDA version provides practical need-to-know content, from the front lines of the wards, for those who are just learning the basics of clinical medicine.
System requirements: Macintosh OS 7 or greater with 20 megabytes of free space
System requirements: PC compatible running Windows 95/98//NT ME/2000/XP with 20 megabytes of free space
Keywords: Internal Medicine -- CD-ROM